Kajian prestasi pengumpul suria Fotovoltan-Terma (PV/T)dengan pelat penyerap lengkuk-v - Mohd Yusoff Haji Othman,; Hafidz Ruslan,; Kamaruzzaman Sopian,; Goh, Li Jin (Universiti Kebangsaan Malaysia, 2009)
A hybrid photovoltaic-thermal solar collector has been designed, built and its performance has been studied. The advantage of the collector is that it can generate electricity and heat simultaneously. Photovoltaic module SHARP NE-80E2EA with maximum output power of 80 W was used to generate electricity. The module also acts as heat absorber of the collector. Single pass ∇-groove collector made of aluminium sheet with 0.7 mm thickness has been used to collect heat generated. Study was conducted under a designed halogen lamps solar simulator with intensities set at 386 ± 8 Wm-2 and 817 ± 8 Wm-2. The speed of air passing through the collector was set between (69.6 ± 2.2) × 10-4 kg/s to (695.8 ± 2.2) × 10-4 kg/s. The objective of the study is to compare the performance of PV/T collector with and without ∇-groove absorber. The study found that the PV/T collector with ∇-groove absorber plate has higher efficiency than the PV/T without ∇-groove absorber. The electrical and thermal efficiencies are also increased when radiation intensity and speed of air increase.